ESTIMASI STOK KARBON PADA VEGETASI HUTAN RAWA GAMBUT DI KAWASAN LINDUNG IUPHHK-HTI PT. MUARA SUNGAI LANDAK KABUPATEN MEMPAWAH PROVINSI KALIMANTAN BARAT - Hidayat, Mohammad Taufiq; Astiani, Dwi; Dewantara, Iswan (Universitas Tanjungpura, 2019)
Carbon stock is carbon stored both on the ground and land surface as plant biomass, dead plants (necromas), and in soil as soil organic matters. Change in carbon form becomes the basis for calculating emissions, where most of the carbon (C) elements that broken down into the air are usually bound to O2 and become CO2. Deforestation and degradation are the main threats on forest conservation in Indonesia. Deforestation and forest degradation that occur in Indonesia has led to the development of issues as a significant contributor to carbon emissions. The purpose of this study is to estimate carbon stocks in protected area at PT. Muara Sungai Landak Mempawah Regency, West Kalimantan Province. This study used non-destructive sampling. This method, was done by measuring the diameter of the tree and then using an allometric equation that is suitable for estimating biomass. The making of sample plots in this study is stratified on land cover condition and systematic sampling. The results show that carbon stock for the entire area/cover of the protected area of PT. Muara Sungai Landak is 25.970.08 tons. The highest carbon was in old shrubland cover with total of 15.425.15 tons, followed by young thicket 10.356.46 tons C. The smallest stock was in open peat land of 188.46 tons C. The calculation of vegetation in this study show the old shrub cover is 128.8 tons/ha. Keywords: Allometric Equation, Carbon Stock, Protected Area, Stratified Sampling.